1985
DOI: 10.1172/jci112191
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of renin activity and angiotensinogen in rat brain. Effects of dietary sodium chloride intake on brain renin.

Abstract: The purpose of this study was to investigate the biochemistry and the regulation of the brain renin-angiotensin system in the Sprague-Dawley rat. Renin activity and angiotensinogen concentrations (direct and indirect radioimmunoassays) were measured in several brain areas and in neuroendocrine glands. Regional renin activities were measured in separate groups of rats on high and low NaCl diets. Mean tissue renin activities ranged from 2.2±0.6 to 54.4±19.7 fmol/mg protein per h (mean of 7±SD), with the highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Angiotensinogen mRNA is present at high levels in some subregions of the olfactory bulb, and mRNAs for angiotensin receptor 1a and angiotensin receptor 2 are present at moderate levels, whereas ACE1 mRNA is very low in the olfactory bulb (Allen Brain Atlas). Immunoreactive angiotensinogen was also detected in olfactory bulb (45). We have shown here that angiotensin I can be cleaved by CPA6 to produce angiotensin II.…”
Section: Discussionsupporting
confidence: 55%
“…Angiotensinogen mRNA is present at high levels in some subregions of the olfactory bulb, and mRNAs for angiotensin receptor 1a and angiotensin receptor 2 are present at moderate levels, whereas ACE1 mRNA is very low in the olfactory bulb (Allen Brain Atlas). Immunoreactive angiotensinogen was also detected in olfactory bulb (45). We have shown here that angiotensin I can be cleaved by CPA6 to produce angiotensin II.…”
Section: Discussionsupporting
confidence: 55%
“…Due to the extremely low renin activity in the brain, debate has persisted regarding the existence of a functional brain RAS [25], [26]. In this study, we showed that prorenin levels were ten-fold higher than those of renin in the cell lysate.…”
Section: Discussionmentioning
confidence: 59%
“…Ganten et al (15) and Fischer-Ferraro et al (16) published the first reports demonstrating central renin activity. Renin activity is widely distributed in the brain, with the highest levels in the pineal gland, pituitary gland, and pons-medulla (30). Substantial controversy still remains as to the localization of renin-containing cells in the brain.…”
Section: Discussionmentioning
confidence: 99%